A contribution to understanding the origin of platy structure in silty soils under no tillage - Sasal, Maria Carolina; Léonard, Joel; Andriulo, Adrian Enrique; Boizard, Hubert (2017)
In silty soils under no tillage (NT), platy (P) soil structure is widespread and constrains water infiltration. Our objectives were (i) to evaluate how traffic and the presence of crop residues influence P structure development in the field and (ii) to characterize changes in soil structure caused by alternation of wetting and drying (w-d) periods for two topsoil layers of a silty soil and two compaction levels in the laboratory. The five-year field experiment was carried out on a Typic Argiudoll under NT and the structure of the A horizon was analyzed using visual soil evaluation (VSE) both before and five years after two traffic levels were applied to four crop sequences. The laboratory experiment of w-d cycles was carried out with two disturbed layers of a Typic Argiudoll, which was repacked to achieve two different bulk densities, and the columns were subjected to 5, 10, or 15 w-d cycles. In the field experiment, the P structure was clearly identified by VSE and corroborated by shear strength and bulk density measurements. The proportion of P structure increased until about 50% of the A horizon after 5 years, irrespective of the traffic or presence of crop residues at the expense of the Φ structure proportion. In the laboratory, consecutive w-d cycles caused changes in soil volume, cracking of the soil surface, and formation of P structure of variable thickness up to 20 mm, confirming that alternation of w-d periods can cause structural modification of the silty soil, in particular horizontally oriented cracks. The number of w-d cycles increased the thickness of the P structure in the upper layer (R2 = 0.55) and in the compacted treatment (R2 = 0.81). The results obtained constitute important progress in the understanding of the evolution of P structure of silty soils under NT.